The Results of Two Conjoined Twin Separations From January to June 2010 : Case Series - Handayani, Siti; Bangun, Kristaninta; Rayeni, Natasha Ratna (Jurnal Plastik Rekonstruksi, 2012)
Conjoined twins are a rare resulting from late and incomplete division of monozygotic embryonic disk generally after 13th day of fertilization. Most cases of separation are extremely risky and life threatening. We present two successful cases of conjoined twins separations, who were admitted to Cipto Mangunkusumo Hospital, both in early 2010. Lulu-Lala, the abdominophagus conjoined twins and NaylaNabila the Abdominothorakophagus conjoined twins. The successions of this conjoined twins separation depends on the techniques, precautions and the team that works together to treat the patients. One of the separation techniques is the utilization of tissue expander to loosen the skin and so can be close primarily by primary closure. The foremost precaution is the infection control, including preparation and sterilization. Conjoined twins have a particular structural defect. Forty percent of them are stillborn and 35% survive only for one day. The mortality is increased by many causes and the most common cause is infection after surgery. All aspects in the team have to give priority to the sterility to avoid infection of those babies. The efforts to avoid the infections must have been done start from pre-surgery managements until the post-surgery.